Environmental Management/Marketing Research: Bibliographic Analysis - Datu Mohammed; Anggy Giri Prawiyog; Elisa Royani Dewi (Startupreneur Business Digital (SABDA Journal), 2022)
This study identifies, synthesizes and evaluates existing environmental research marketing and management with the ultimate goal of revealing trends in this area. In particular, we focus on: the methodological aspects of empirical research are the design, scope, and methodology, the field of study covered and the specific issues raised in all regions. Related articles are also identified electronically. Manual bibliographic search method. A total of 530 articles from 119 scientists were identified in magazines published from 1969 to 2008. Each article is analyzed with 6 pieces of content: key aspects: author profile, manuscript characteristics, study design, scope research, research methodology and field of study. Overall, this research facility is facing serious problems. Transformation moves from the early stages of identification and discovery to more advanced stages, an advanced stage characterized by greater maturity and rigidity. This is indicated by: trends towards inter-author, intercultural and interdisciplinary collaboration. The length of the manuscript and the number of references increased over time. Grow up maturity of study design with increasing emphasis on formalization and causality structure; various countries, industries, Products and companies of varying status, size, and geographic focus. The tendency to use stochastic sampling designs to achieve high response rates, ensuring large sample sizes, Apply advanced statistical analysis. Wide variety and deep coverage examining the topic.